Peningkatan Hasil Belajar Siswa Dengan Model Problem Based Learning Pada Materi Yesus Mewartakan Kerajaan Allah Di Kelas VIII SMP Pengabdi Singkawang Tahun Pelajaran 2023/2024 - Sri Fransiska (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The main problem occurs for this research is the result of Catholics lesson is too low for 8th grades students in Pengabdi Junior High School for informs the Kingdom of Jesus Christ. The matter appears because of the educator could not stimulus the students’ activation in learning progress until they could not able to increase they abilities and creativities critically, results of learning methods and multimedia for educator still in speech method and common discussion which still monotone until the students feels bored and passive to learn the material, especially about “God’s Kingdom”, seems hard because it needs to analyses their meanings and the goals. This case appears badly in students results, because there are many students could not reach the Criteria of Learning Progress. In other hand, the students’ results become lower and does not fulfill the targets. This research aims is to knowing well their results in Catholics Religion for 8th grades students in Pengabdi Junior High School for informs the Kingdom of Jesus Christ through Problem Based Learning method and to indicate the increasing of their lesson. This research runs in Class Research Methods, which be held in two steps. The sources of Data is from Students results in learning and the observation of students of concern in learning. The progress of action in first step, before using Problem Based Learning method from 20 students, there is 65 % which still lower, although the total of good results just 30%. In evaluation of first steps, the researcher use the Problem Based Learning method, there is 70% the total of good results, and there is 30% of students in lower results. This matter happens significantly in second step which the total of good results become 100%. In results, this research shows there is a good progress for students’ result in learning process from the 1st and the 2nd steps. The presentation of students’ progress in learning happens due to progress of students’ interest in learning process through Problem Based Learning method in learning activities.